A bibliography of terrestrial biological research in Dronning Maud Land, Antarctica - Newton, I P; Cooper, J; Mehlum, Fridtjof; Thor, Göran (South African Journal of Antarctic Research, 1994)
A bibliography of terrestrial biological research in Dronning Maud Land, Antarctica, of 388 titles from 1954 to 1994 is provided as an aid to researchers working in the region.
Keywords: Dronning Maud Land; bibliografi; biologi